The VPS-20 Subunit of the Endosomal Sorting Complex ESCRT-III Exhibits an Open Conformation in the Absence of Upstream Activation - Schuh, Amber L. (Biochem J, 2015)
Members of the endosomal sorting complex required for transport (ESCRT) machinery function in membrane remodeling processes during multivesicular endosome biogenesis, cytokinesis, retroviral budding, and plasma membrane repair. During lumenal vesicle formation at endosomes, the ESCRT-II complex and the ESCRT-III subunit VPS-20 play a specific role in regulating assembly of ESCRT-III filaments, which promote vesicle scission. Previous work suggests that Vps20 isoforms, like other ESCRT-III subunits, exhibits an autoinhibited, closed conformation in solution, and its activation depends on an association with ESCRT-II specifically at membranes. However, we show here that C. elegans ESCRT-II and VPS-20 interact directly in solution, both in cytosolic cell extracts and using recombinant proteins in vitro. Moreover, we demonstrate that purified VPS-20 exhibits an open, extended conformation, irrespective of ESCRT-II binding, in contrast with the closed, autoinhibited architecture of another ESCRT-III subunit, VPS-24. Our data argue that individual ESCRT-III subunits adopt distinct conformations, which are tailored for their specific functions during ESCRT-mediated membrane reorganization events.